An Evaluation of Acute and Subchronic Toxicities of a Nigerian Polyherbal Tea Remedy - Ogbonnia, Steve O.; Mbaka, Godwin O.; Anyika, Emmanuel N.; Emordi, Jonathan E.; Nwakakwa, Ndubuisi; Nwakakwa, Ndubuisi (Pakistan Journal of Nutrition, 2011)
The evaluation of the acute and subchronc toxicities of a Nigerian polyherbal tea remedy, prepared with Anthocleista vogelii, Ficus exasperata leaves and Viscum album (mistletoe), was carried out in Swiss albino mice and Wistar rats of both sexes. The lyophilized extract in the dose ranges of 1.0 g to 20.0 g/kg body weight was administered orally to the mice and observed continuously for the first 4 h and hourly for the next 12 h, then 6 hourly for 56 h (72 h, acute toxicity). Wistar rats were also fed with different doses of the lyophilized formulation for 30 days and the effects on some tissues - heart, liver and testes - were histologically evaluated. Also the effects on the biochemical and haematological parameters were evaluated (subchronic toxicity model). The median acute toxicity value (LD50) of the polyherbal tea was determined to be 8.970 g/kg body weight. The tea significantly reduced (p